Skills and Techniques of Machine Repair Fitters - Zhou, Aimin (Journal of Theory and Practice of Engineering Science, 2024)
In this important understanding of machining, mechanical maintenance fitter occupies an important position. Machine repair fitters are mainly responsible for the processing and maintenance of various mechanical equipment, and use scientific control methods to restore mechanical properties. Therefore, we can see that the faults in machine maintenance need quick maintenance by fitters to solve various problems that often occur in machine maintenance. In this case, the fitter must master basic machine maintenance skills and use excellent information technology to assist in the installation of various machines. Therefore, this article gives a brief introduction to the machine fitters used for machine maintenance and shows how to increase their repair capacity to make machine maintenance more efficient. With the progress of scientific and the rapid increase in productivity, competition between enterprises is more and more intense. If enterprises want to maintain a high competitiveness and advantages, they need to focus on the research and development of core technology of their companies and improve core competitiveness. So in such a large background, many companies choose to focus on the development of their core business, and then they need other enterprises to complete their own non-core business resources. In such a development process, the logistics industry will gradually separated and then the third-party logistic enterprises show up.